2007
DOI: 10.1097/qai.0b013e3180decbe2
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Pneumocystis jiroveci Pneumonia in Italian AIDS Patients

Abstract: The present data suggest the absence of a correlation between P jiroveci ITS types and specific clinical characteristics. DHPS mutations correlate with possible failure of anti-P jiroveci sulfa therapy, and a trend of association is shown between DHPS mutations and some clinical PcP features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 36 publications
2
17
1
Order By: Relevance
“…There are however, a few potential reasons why Pneumocystis DHPS mutant infection was not associated with a significant increase in mortality in our study. First, our study had a higher prevalence of mixed DHPS infections (21%) compared to prior studies that have observed an association between DHPS mutant infection and death (prevalence range: 0–3%) [911]. The higher prevalence of mixed infections observed in our study may have potentially impacted a mortality difference from being observed.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…There are however, a few potential reasons why Pneumocystis DHPS mutant infection was not associated with a significant increase in mortality in our study. First, our study had a higher prevalence of mixed DHPS infections (21%) compared to prior studies that have observed an association between DHPS mutant infection and death (prevalence range: 0–3%) [911]. The higher prevalence of mixed infections observed in our study may have potentially impacted a mortality difference from being observed.…”
Section: Discussioncontrasting
confidence: 48%
“…Only four studies have found no association with sulfa prophylaxis and DHPS mutant. Interestingly, all four studies may have defined sulfa prophylaxis differently from those definitions used in this study: two studies did not define prophylaxis duration [17,18] while two studies defined prophylaxis as sulfa use for a minimum of one week in the six months preceding PCP diagnosis [9,19]. Furthermore, one study observed a higher prevalence of mixed infections relative to pure mutant infections [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations